ADHD Comorbidity, Gender, and Symptom Profiles - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The results of the NIMH Collaborative Multisite Multimodal Treatment Study of Children with Attention-Deficit/Hyperactivity Disorder (MTA) have been reexamined from several standpoints.